Understanding the accelerated weathering response of thermoplastic composites - Lee, Pei Ying (Nanyang Technological University, 2023)
Glass fibre reinforced polymer (GFRP) has been extensively used over the years which requires the reliability and service lifetime to be determined. Former studies on using different fillers, polymers and how properties changed after weathering have been presented. However, most have investigated on a different combination of polymers, fillers, and weathering method of these FRPs to understand the influence of weathering, indicating the presence of a research gap. In this thesis, the effect of polypropylene (PP) and Poly (ethylene glycol-co-1,4-cyclohexanedimethanol terephthalate) (PETG) with the addition of glass fibres (GFs) under accelerated weathering conditions were investigated. This will provide insight in understanding the critical parameters influencing the material properties in FRP for future studies. This eventually helps to detail the acceleration factors that are in play. Samples were irradiated in the QUV with UVA lamp for 21 weeks in 2-week increments. Two different irradiance levels, 0.83 W/m2/nm from week 0 - 11, and 1.66 W/m2 /nm from week 11 – 21 were employed. Their visual appearances, colour changes, mechanical and chemical changes had been analysed before and after weathering. Mechanical properties were investigated with Tensile Testing and Flexural Testing. Colour measurement of the PETG/GF surfaces were carried out by measuring CIELAB parameters (L*, a*, b* and ∆E*). The thermal characteristics of the GRFPs were investigated using differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). With the use of attenuated total reflectance fourier transform-infrared (ATR-FTIR), the modifications in the surface chemical groups of the GRFPs were identified. From the results obtained in this study conducted, it has shown that photo oxidation, thermo oxidation and hydrolytic degradation had indeed occurred on the surface for both FRPs throughout the accelerated weathering process. This revealed the importance of the combined exposure of UV radiation, heat, and cool cycle to GRFP degradation. Unfortunately, the objective to determine the critical weathering and acceleration factors could not be achieved. Further characterisations on the surface and core are required to be conducted to enhance its significance.